Hip arthroscopy utilization and associated complications: a population-based analysis - Degen, Ryan M. (J Hip Preserv Surg, 2017)
The purpose of this study is to review the trends in hip arthroscopy using data from a statewide database, focusing on utilization rates, patient demographics and complication rates. The Statewide Planning and Research Cooperative System (SPARCS) database for New York State was queried for cases of hip arthroscopy from 1998 to 2012. Patient demographics and procedural details were collected. Patients were subsequently reviewed for complications and readmissions within 30 and 90 days. In total, 12 194 hip arthroscopy procedures were performed by 295 surgeons in 137 centers between 1998 and 2012. There was a 95-fold increase in the annual frequency of hip arthroscopy procedures between 1998 (n = 24) and 2012 (n = 2296). Thirty-day complication rates were 0.2% (n = 19), whereas the 90-day complication rate was 0.3% (n = 30). The all-cause 30-day readmission rate was 0.5% (n = 66), whereas the 90-day rate was 1.6% (n = 200). The number of surgeons performing hip arthroscopy increased 7-fold over the observation period. However, only 14.9% (n = 44) of surgeons performed more than 30 procedures annually. Lower volume surgeons (<102 cases/year) demonstrated significantly higher 90-day readmission rates, compared with higher volume surgeons (>163 cases/year, P < 0.0060); however, complication rates and readmission rates did not differ based on surgeon volume. Our findings confirm our hypothesis, demonstrating a significant increase in utilization of hip arthroscopy in the State of New York. We did not identify an associated increase in annual complication rates as hypothesized with increasing utilization, although there was an association of higher readmission rates among lower volume surgeons. Further study is needed to define rates of failure requiring revision hip arthroscopy or conversion to arthroplasty, and to clarify the relationship between complication rates and surgeon volume and case complexity. Level of Evidence: III, retrospective cohort series.